Evaluation of 2G and 4G Cellular Network Performance Along the Trans Padang–Bungus Route - Tri Sukma Afani; Muhammad Putra Pamungkas; Yulindon (International Journal of Wireless And Multimedia Communications, 2026)
The quality of mobile telecommunication services is a vital parameter in supporting the connectivity of public transport passengers, particularly on routes with significant topographical challenges. This study aims to evaluate the performance of 2G and 4G LTE networks along the Transpadang Bungus Corridor route in Padang City to map signal quality and identify areas with low performance. The research materials involve the use of hardware in the form of smartphones integrated with TEMS Pocket software for field data collection, as well as TEMS Discovery for statistical data processing and geographical visualization. The method employed is a continuous drive test along the route to collect technical parameters in real-time. Measurement results indicate that on the 2G network, the RxLev parameter is dominated by the "Good" category ([-80, -70] dBm) at 25.62%, with exceptionally high RxQual stability reaching 87.53% in the "Excellent" category. However, on the 4G LTE network, the RSRP parameter shows coverage challenges where 14.03% of samples fall into the "Very Poor" category ([Min, -110] dBm) and 23.87% into the "Poor" category ([-110, -100] dBm), particularly in areas with geographical obstructions. RSRQ quality remains at a moderate level with 50.66% of samples in the [-15, -10] dB range, while data throughput is dominated by the 1000-7000 kbps range at 78.5%. The implications of this research provide strategic recommendations for cellular operators to perform optimization through antenna tilting adjustments or capacity increases in critical areas to enhance the user experience on the Transpadang route.